Analysis of the Adsorption Behaviour of Cadmium on Aluminium-Pillared Diatomite in a Solid/Liquid System Using Classical Adsorption Theory - Jian Zhu; Ping Wang; Mingjing Lei; Weili Zhang; Taoyuan Wang; Xiaofu Wu (Adsorption Science & Technology, 2013)
A readily available effective adsorbent is necessary to adsorb heavy-metal ions from aqueous solutions. In this study, a novel adsorbent with good adsorption properties [Al 3+ –oligomer–pillared diatomite (Al 3+ –oligomer–PD)] was prepared and was used to adsorb Cd 2+ ions in a solid/liquid system. The property and nature of the Cd 2+ ions adsorbed on the surface of the Al 3+ –oligomer–PD were studied by performing a series of adsorption tests and related surface property analyses. Our study results show that owing to a more favourable pore structure, the PD has a higher adsorption property compared with natural diatomite (ND) and most other common adsorbents. The adsorption capacity of PD is 27.36% greater than ND and also achieves an optimal value of 10.05 mg/l. Certain parameters have a significant effect on Cd 2+ ion adsorption. The most suitable isotherm and kinetics models for describing the adsorption of Cd 2+ ions are the Freundlich and pseudo-second-order models. The nature of Cd 2+ ion adsorption on PD is favourable, physical, spontaneous, exothermic and disorder increasing. The results of the study suggest that PD is an ideal adsorbent for the removal of cadmium ions from aqueous solutions.